The development of an in vivo nerve-muscle model in the rat : and an experiment "The interaction between rocuronium and thiopentone" to test the validity of the model - Rous, Stephen Alexander (Department of Anaesthesia, 2014)
Includes bibliographical references (leaves 55-59).